PENERAPAN MODEL SIMULASI ANTRIAN MULTI CHANNEL SINGLE PHASE PADA ANTRIAN DI APOTEK PURNAMA SEMARANG - Aji, Soma Purnama; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The purpose of this study was to investigate and analyze service level on thePharmacy assistant pharmacist Purnama Semarang. The data was required in the form of primarydata, the number of patients who come in and is served every weekday. The data was obtainedthrough the observation of which the period was conducted from June 1 to June 30, 2012 from 3:00pm until 9:00 pm. The analysis technique used was multichannel singlephase simulation. The resultsusing multichannel single phase simulation model showed that the expected number of patientsqueuing in the system 3 and Pharmacy Purnama Semarang need to perform additional servicefacilities, the addition of pharmacy assistants from initially taking four to seven pharmacistassistants. At every hour of work with the addition of this decrease patient waiting time before 19minutes 5 seconds to 10 minutes 36 seconds, so that service performance can be achieved accordingto standard set.Keywords: Simulation, Queue, Pharmacist assistants